Standardized Complex Gut Microbiomes Influence Fetal Growth, Food Intake, and Adult Body Weight in Outbred Mice - Christa N. Cheatham; Kevin L. Gustafson; Zachary L. McAdams; Giedre M. Turner; Rebecca A. Dorfmeyer; Aaron C. Ericsson (Microorganisms, 2023)
Obesity places a tremendous burden on individual health and the healthcare system. The gut microbiome (GM) influences host metabolism and behaviors affecting body weight (BW) such as feeding. The GM of mice varies between suppliers and significantly influences BW. We sought to determine whether GM-associated differences in BW are associated with differences in intake, fecal energy loss, or fetal growth. Pair-housed mice colonized with a low or high microbial richness GM were weighed, and the total and BW-adjusted intake were measured at weaning and adulthood. Pups were weighed at birth to determine the effects of the maternal microbiome on fetal growth. Fecal samples were collected to assess the fecal energy loss and to characterize differences in the microbiome. The results showed that supplier-origin microbiomes were associated with profound differences in fetal growth and excessive BW-adjusted differences in intake during adulthood, with no detected difference in fecal energy loss. Agreement between the features of the maternal microbiome associated with increased birth weight here and in recent human studies supports the value of this model to investigate the mechanisms by which the maternal microbiome regulates offspring growth and food intake.